1999
DOI: 10.1016/s0735-1097(99)00003-0
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis of the thoracic aorta and aortic debris as a marker of poor prognosis: benefit of oral anticoagulants

Abstract: We confirm the high incidence of vascular events and deaths in patients with AA. We have demonstrated, for the first time in this condition, a better outcome among patients treated with oral anticoagulants versus antiplatelets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
115
1
5

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(127 citation statements)
references
References 23 publications
2
115
1
5
Order By: Relevance
“…15 However, the proper therapy for this condition is unknown so far. In smaller, nonrandomized studies, oral anticoagulants were superior to aspirin, 20,21 whereas in a larger retrospective, nonrandomized analysis, only statins showed a significant benefit. 22 The ongoing Aortic arch Related Cerebral Hazard (ARCH) trial comparing clopidogrel plus aspirin versus warfarin will contribute substantial information for the optimal treatment and might increase the diagnostic impact of TEE.…”
Section: Clinical Implications Of Cardiac High-risk Sources In Teementioning
confidence: 95%
See 1 more Smart Citation
“…15 However, the proper therapy for this condition is unknown so far. In smaller, nonrandomized studies, oral anticoagulants were superior to aspirin, 20,21 whereas in a larger retrospective, nonrandomized analysis, only statins showed a significant benefit. 22 The ongoing Aortic arch Related Cerebral Hazard (ARCH) trial comparing clopidogrel plus aspirin versus warfarin will contribute substantial information for the optimal treatment and might increase the diagnostic impact of TEE.…”
Section: Clinical Implications Of Cardiac High-risk Sources In Teementioning
confidence: 95%
“…19,20 However, there is no evidence based treatment for this situation so far. With disappearance of aortic thrombi in TEE control 4 weeks later, medication was changed to platelet inhibitors plus statins for plaque stabilization in our patients.…”
Section: Clinical Implications Of Cardiac High-risk Sources In Teementioning
confidence: 99%
“…Earlier studies reported a potential benefit of anticoagulation. 30,31 On the other hand, Tunick et al 32 found no significant benefit of anticoagulant or antiplatelet drugs for patients with ACL. A large prospective study is needed to determine which of these are better for patients with ACL.…”
Section: Discussionmentioning
confidence: 99%
“…Complex plaques more than 4mm in diameter, mobile or ulcerated are more likely to embolise and had higher recurrent stroke rate (23)(24)(25)(26)(27). Options of treatment are AC, the use of antiplatelet therapy or surgical resection (24,25,28). Current evidence favours the use of AC with surgery being considered in highly selected cases.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%